Asociaciones vegetales en el manglar de la Barra de Santiago, Ahuachapán, El Salvador - Molina Lara, Oscar Armando; Esmeralda Esquivel, Rhina (Revista de Biología Tropical, 1993)
A mangrove swamp was studied (Sep. - Dec. 1986) al Barra de Santiago Ahuachapan, El Salvador. Twent2 stations oi 1000 m2 each were sampled. A random stratified square metnod was used with fOUT quadrants oi 250 m for eaen station. The analysis included floristic arboreal composition, structural development and zonation pattem. In agreement with the analysis of conglomerates, the identified specimens represent five associations. Rhizophora racemasa and Rhizophora mangle form the outer margin of the subtidal region in continuosly submerged zones. This is followed by’associations of Avicennia germinans and R. racemasa in regions near and at a distance from the canal with intermediate inundations. After fuese are the associations of Avicennia bicolor and A. germinans in non-inundated ro nes without mudo Finally there are associations of Laguncularia racemasa and A. germinans in regions totally removed from the canals. The productivity of vegetation of the rnangrove swamps in terms of the basal area was 30 m2Jha with average heights between 7.3 ± 2 rn and 18 ± 6.3 m.